1993
DOI: 10.1029/92jd02384
|View full text |Cite
|
Sign up to set email alerts
|

The total reactive oxidized nitrogen levels and the partitioning between the individual species at six rural sites in eastern North America

Abstract: During the late summer and early fall of 1988, measurements of many trace species of tropospheric photochemical interest, including NO, NO2, PAN, HNO3, NO3-, NOy, and ozone were made at seven surface stations in the eastern United States and Canada. The NOy (as well as ozone) levels and its partitioning were strongly influenced by the diurnal evolution of the boundary layer at the sites that are beneath the nocturnal inversion. At the higher elevation sites the median levels of all species were much more nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(79 citation statements)
references
References 35 publications
6
71
2
Order By: Relevance
“…5. By grouping the data according to the correlation (negative, positive and non-related), an improved positive correlation R 2 = 0.54 with ∆O3/∆CO = 0.560±0.0156 ppbv/ppbv can be calculated, which is slightly higher than other measurements (the order of 0.3 ppbv/ppbv) at Izaña observatory, Tenerife, by Fischer et al [32] and in eastern North American by Parrish et al [33] and by Chin et al [34], but consistent with observations ranging from 0.17-0.62 and 0.20-0.69 reported by Wofsy et al [35] and by Mauzerall et al [36] observed at surface sites in eastern North America, respectively, as well as 0.4 to 1.0 observed over the eastern United States by Zhang et al [37]. The negative correlation observed during the night hours for CO values over 100 ppbv might indicate a downward transport of the polluted air to the measurement site after photochemical processing or the O3 titration by the NO, associated with the freshly emitted CO.…”
Section: Correlation Between Co and O3mentioning
confidence: 87%
“…5. By grouping the data according to the correlation (negative, positive and non-related), an improved positive correlation R 2 = 0.54 with ∆O3/∆CO = 0.560±0.0156 ppbv/ppbv can be calculated, which is slightly higher than other measurements (the order of 0.3 ppbv/ppbv) at Izaña observatory, Tenerife, by Fischer et al [32] and in eastern North American by Parrish et al [33] and by Chin et al [34], but consistent with observations ranging from 0.17-0.62 and 0.20-0.69 reported by Wofsy et al [35] and by Mauzerall et al [36] observed at surface sites in eastern North America, respectively, as well as 0.4 to 1.0 observed over the eastern United States by Zhang et al [37]. The negative correlation observed during the night hours for CO values over 100 ppbv might indicate a downward transport of the polluted air to the measurement site after photochemical processing or the O3 titration by the NO, associated with the freshly emitted CO.…”
Section: Correlation Between Co and O3mentioning
confidence: 87%
“…Ozone to CO ratios have previously been used to estimate the amount of O 3 exported to the North Atlantic troposphere from North America (Parrish et al, 1993;Parrish et al, 1998). With a tropospheric lifetime of about 2 months, CO is a long-lived tracer of anthropogenic sources and therefore can help to differentiate between O 3 sources.…”
Section: O3/co Ratios: Influence Of Air Mass Origin and Dustmentioning
confidence: 99%
“…The afternoon NOx* levels were found to approach NOy at several rural sites in eastern United States, with aerosol nitrate contributing less than 10% to total NO,. [Parrish et al, 1993a]. It is possible that particulate nitrate has a larger contribution to NOy in China due to the higher loading of particles (which can absorb and react with gas-phase nitric acid).…”
mentioning
confidence: 99%